2010
DOI: 10.1039/c0gc00118j
|View full text |Cite
|
Sign up to set email alerts
|

Extractive desulfurization of fuel oils with low-viscosity dicyanamide-based ionic liquids

Abstract: Four low-viscosity ionic liquids (ILs) based on the dicyanamide anion ([N(CN) 2 ] -), i.e., 1-butyl-3-methylimdazolium ([BMI][N(CN) ), have been investigated to determine their extraction capability for thiophene (TS) and dibenzothiophene (DBT) from model fuel oils. Aromatic imidazolium is more efficient than cyclic thiophenium and tetrahedral trialkylsulfonium; specifically, the S-extraction ability follows the orderwith DBT being more efficiently extracted than TS. The S-extraction of [BMI][N(CN) 2 ] has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(76 citation statements)
references
References 79 publications
7
69
0
Order By: Relevance
“…Rather, the characteristic nature of the solvents involved vis-à -vis their relative affinity towards the solute (in this case sulfur compounds) determine the driving force and its direction. Asumana et al [21] and many other research groups [5], [15], [22]- [24] made similar findings in their works related to desulfurization of liquid fuels with ionic liquids. …”
Section: B Effect Of Extraction Variables On the Extraction Efficiensupporting
confidence: 60%
“…Rather, the characteristic nature of the solvents involved vis-à -vis their relative affinity towards the solute (in this case sulfur compounds) determine the driving force and its direction. Asumana et al [21] and many other research groups [5], [15], [22]- [24] made similar findings in their works related to desulfurization of liquid fuels with ionic liquids. …”
Section: B Effect Of Extraction Variables On the Extraction Efficiensupporting
confidence: 60%
“…With wide-ranging applications in separation technology, nanotechnology, catalysis, electrochemistry, etc., ILs are being acclaimed as "green" and "designer" solvents. [26][27][28] Several ILs have been studied as solvent in EDS for S-removal from fuel oils such as [1-butyl-3- 37 Compared with EDS alone using ILs, some researchers observed that ODS is much more efficient and S-removal can be increased up to 90% from 10-40% in EDS, such as [butyl-6-methylquinolinium (Bmimquin)]DCA in ODS process removed 99.9% of S-contents at mild conditions from model diesel fuel. 38 In a typical ODS, S-compounds in gasoline fuel are extracted into the IL phase first, then oxidized by some oxidant, and the oxidized product is more polar and easily removable.…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium time is short and may serve well for industrial process to generate large quantities of low-sulfur oil. [35,46,75] For three sulfur compounds, the best extraction time is 20 or 30 min considering both the extraction efficiency and time cost, so in further researches, the extraction time is set at 30 min, which is also in accordance with previous experiments and more than sufficient to establish extraction equilibrium.…”
Section: Extraction Timementioning
confidence: 87%
“…Therefore, the extraction capability of [MMP][DMP] is insensitive to temperature. There are two reasons for this phenomenon: First, the viscosity of ionic liquid would decrease with increasing temperature, which would promote the liquid-liquid contact between IL and fuel oil, thus improving the extraction performance; [46,[76][77][78][79] second, according to Xu's theory, [80] in a simple extraction where the extracts maintain the same form in both phase, the partition coefficient can be denoted as…”
Section: Extraction Temperaturementioning
confidence: 99%